2019
DOI: 10.3233/jad-190894
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Blood Ethylmercury Levels and Cognitive Decline Among Older Adults and the Elderly in the United States

Abstract: Cognitive health is an emerging public health concern for the aging American population. Mercury (Hg) is a toxic element that can cause nervous system damage. This hypothesis-testing study evaluated the relationship between blood ethyl-Hg levels and cognitive decline in an older adult and elderly American population. A total of 1,821,663 weighted-persons between 60–80 years old with detectable blood ethyl-Hg levels within the 2011–2012 National Health and Nutritional Examination Survey were examined. Those per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Interestingly, following a detoxification dietary regime, his memory partially improved as the levels of mercury dropped in his body (Foley et al, 2020). Accordingly, in another study the authors found a positive correlation between the blood levels of ethylmercury and cognitive decline in older adults and elderly American populations (Geier et al, 2019). Furthermore, other evidences also support a possible long-term effect of mercury toxicity due to pre or perinatal exposure.…”
Section: Methylmercury Targets Brain Neurogenesis? Possible Implicatimentioning
confidence: 93%
“…Interestingly, following a detoxification dietary regime, his memory partially improved as the levels of mercury dropped in his body (Foley et al, 2020). Accordingly, in another study the authors found a positive correlation between the blood levels of ethylmercury and cognitive decline in older adults and elderly American populations (Geier et al, 2019). Furthermore, other evidences also support a possible long-term effect of mercury toxicity due to pre or perinatal exposure.…”
Section: Methylmercury Targets Brain Neurogenesis? Possible Implicatimentioning
confidence: 93%
“…Con respecto a las enfermedades del sistema nervioso, estas son las que presentan efectos más visibles, mediante la odds ratio; sobresale el deterioro cognitivo en adultos (Geier et al, 2019). Esto podría deberse a que los adultos mayores acumulan más cantidad de Hg en su organismo con la edad, por lo cual dicha población es especialmente susceptible.…”
Section: Efectos Negativos En La Salud Atribuidos a La Exposición Al ...unclassified
“…Geier DA, et al, in their study provide epidemiological data, which linked the increase of ethyl-mercury levels in the blood with the cognitive impairment of the elderly ( 27 ). Also, Sun YH, et al, conducted a study in which they discovered that individuals who were exposed to mercury via dental amalgam, had an increased ratio of 1,132 on developing Alzheimer’s disease, in comparison to those who were not exposed at all ( 28 ).…”
Section: Toxic Environmental Factorsmentioning
confidence: 99%